WOMEN EMPOWERMENT THROUGH GREEN LEAFY VEGETABLES BUSINESS IN VELLORE - V, SWETHA; R, AARTHI; J, GODWIN CHRISTOPHER; S, USHA. (International Journal of Psychosocial Rehabilitation, 2020)
Vellore is a home to varieties of green leafy vegetables. This region is blessed with a range of traditional varieties of nutritious greens. But till today there has been very less documentation of their use and hence their complete benefits are not known leading to its underutilization. Thus there is a need to document the types of green leafy vegetables to analyze their uses and quantification. About sixteen varieties of green leafy vegetables were commonly found in the locality of Vellore which includes Amaranthus caudatus, Solanum nigrum, Alternanthera sessilis, Amaranthus gangeticus, Sesbania grandiflora, Spinacia olerecea, Amaranus dubius, Eclipta alba, Hibiscus cannabis, Portulaca olerecea, Centella asiatica, Moringa oleifera, Coriandum sativum, Murraya koenigii, Mentha arvenis and Trigonella foenum. This business of green leafy vegetable also promotes women empowerment or rehabilitation as this business is mostly done by women. This study helps the reader get an overview of green leaf availability, quantity, nutritive and medicinal properties of leafy green vegetables business in Vellore, South India.